PERHITUNGAN TITIK IMPAS (BREAK EVENT POINT) DENGAN METODE MARGIN KONTRIBUSI SEBAGAI ALAT PERENCANAAN LABA - suprajitno, Dwi (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2015)
Calculation of break even or recoup their calculation or computation known as the break-even points is one financial calculation that is very important in financial planning firm. Break Even Point (BEP) can be defined as a point or state where the company in its operations do not benefit and not suffer a loss. In other words, the state of gain or loss equal to zero. Contribution margin is the difference between the sales value of the variable costs. Contribution margin can be used to cover the fixed costs, and when they left the rest is profit. If managemen wants to know the breakeven sales quantity, the amount of the total countribution margin should be equal to the total amount of fixed cost. Bakers "Bayu Sari" Petanahan is a manufacturing company engaged in the production of the production of bread. This company is mass produced bread and orders from consumers either in bulk or small. Therefore the company requires the calculation of the break-even point in order to generate accounting information useful for short-term profit planning.   Keywords: break-even point, fixed costs, variable costs, contribution margin